2000
DOI: 10.1080/09640560020001665
|View full text |Cite
|
Sign up to set email alerts
|

Economic Valuation of the Non-use Attributes of a Wetland: A Case-study for Lake Kerkini

Abstract: Wetlands are an environmental feature which deliver a variety of market and non-market goods and services. Established environmental economic theory separates the value of these goods and services into direct-use values, indirect-use values and non-use values. Given appreciation of all three, measurements can be derived to demonstrate the amount of public money that it may be feasible to allocate to the sustainable management of wetlands. However, in many cases, non-use values are ignored and the total economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 14 publications
0
27
0
2
Order By: Relevance
“…Several other studies also found positive relationship between these variables. For example, positive impact of income on WTP is witnessed in studies by Westerberg et al, 2010;Ghosh and Mondal, 2012;Birol et al, 2006;Othman et al, 2004;Birol et al, 2011;Hanley et al, 2006;Oglethorpe and Miliadou, 2000;Bliem et al, 2012 andNuva et al, 2011.The positive effect of membership in NGO on WTP also reported by Oglethorpe and Miliadou 2000;Pattison et al 2011. The negative interaction between number of people per household with the level 3 of natural scenery indicates that large families have lower WTP compare to small size families. Our results were similar to some other previous studies (Perez-Verdin et al, 2011;Hammitt et al, 2001;Pattison et al, 2011).…”
Section: Results Of the Choice Experimentsmentioning
confidence: 70%
“…Several other studies also found positive relationship between these variables. For example, positive impact of income on WTP is witnessed in studies by Westerberg et al, 2010;Ghosh and Mondal, 2012;Birol et al, 2006;Othman et al, 2004;Birol et al, 2011;Hanley et al, 2006;Oglethorpe and Miliadou, 2000;Bliem et al, 2012 andNuva et al, 2011.The positive effect of membership in NGO on WTP also reported by Oglethorpe and Miliadou 2000;Pattison et al 2011. The negative interaction between number of people per household with the level 3 of natural scenery indicates that large families have lower WTP compare to small size families. Our results were similar to some other previous studies (Perez-Verdin et al, 2011;Hammitt et al, 2001;Pattison et al, 2011).…”
Section: Results Of the Choice Experimentsmentioning
confidence: 70%
“…Passive values and the value of supporting various types of recreational activities were elicited by means of CVM. The value of supporting recreational activities ranged between 687 USD/ha/annum in Lac du Der, France (Scherrer 2003) and 2,048 USD/ha/annum in India (Verma 2001), while passive value estimates for Lake Kerkini in Greece were as high as 9,144 USD/ha/annum (Oglethorpe and Miliadou 2000).…”
Section: The Literature On Values Of Human-made Wetlandsmentioning
confidence: 99%
“…In order to select the best management option for achieving sustainable fish biodiversity management, some studies have been done by Ruitenbeek (1992), Stevens et al (1995), Oglethorpe and Miliadou (2000), and Rizal et al (2001). These studies used Cost-benefit analysis in comparing each management option.…”
Section: Resultsmentioning
confidence: 99%